Understanding Performance Efficiency in ISO/IEC 25000: A Systematic Literature Review - Rojas, Hesmeralda; Renteria, Ronald; Martinez, Virgilio (Society of Visual Informatics, 2025)
Performance efficiency is a critical aspect of software quality, particularly in modern applications handling large data volumes, simultaneous users, and complex operations. This study aimed to provide a comprehensive overview of current research on performance efficiency under ISO/IEC 25010. This involved examining the topics driving this research, alongside their contexts, objectives, applications, tools, and metrics, enabling the visualization of emerging trends in the quantification and evaluation of performance efficiency. To this end, a systematic literature review was conducted from 2014 to 2024, following a protocol that combined automated and manual searches. This process yielded 38 primary studies. The results revealed five central research topics, with time behavior identified as the most studied sub-characteristic (48%), followed by resource utilization (36%) and capacity (16%). The study also analyzed the reasons for this distribution of research interest. A total of 68 metrics were identified: 41 related to time behavior, 16 to resource utilization, and 11 to capacity. Additionally, 46 tools were identified for evaluating these three sub-characteristics. This analysis provides a solid foundation for objectively measuring and comparing software performance. The findings of this study offer a holistic view of performance efficiency. From an academic perspective, it supports the development and validation of research in software engineering. It provides a comprehensive understanding of ISO/IEC 25010, facilitating systematic improvements and tracking its evolution. From an industry perspective, it serves as a practical resource for enhancing competitiveness by promoting compliance with the standard and improving knowledge of performance efficiency.